Implementation of Improvement of Building Rights into Land Ownership Rights and its Obstacles in Indonesia - Krismantoro, Damianus; Hutapea, Maria; Joe, Christian (Westscience Press, 2025)
Building Rights Title (HGB) which has expired according to the legislation will return to the original legal status of the land rights, namely returning to state land, management rights or individuals. The problem in this study is how the implementation of an increase from Building Rights Title to Land Ownership Rights in Indonesia, and what obstacles arise in increasing land rights. The research method used is normative juridical. The data source used is secondary data. The data collection method is done by means of literature study. Data processing is done by descriptive analytical method. Land with HGB status can be upgraded to Property Rights by applying for an increase in rights. However, in reality not all HGB can be upgraded to Property Rights. HGB that is on the land of a person's property rights and land management rights can not be upgraded to Property Rights. In addition, HGB that is encumbered with a mortgage cannot be upgraded to Hak Milik as long as the debt has not been repaid.